A study on balanced chromosomal translocations in couples with recurrent pregnancy loss - Pritti K Priya; Vineet V Mishra; Priyankur Roy; Hetvi Patel (Wolters Kluwer Medknow Publications, 2018)
Background: Recurrent pregnancy loss (RPL) is an obstetric complication that affects couples in their reproductive age. Chromosomal abnormalities, mainly balanced rearrangements, could commonly be present in couples with RPL. Aim: The purpose of this study is to evaluate the contribution of chromosomal abnormalities and balanced reciprocal translocations, in particular occurring in either of the partners, resulting in RPL. Materials and Methods: A retrospective cytogenetic study was carried out on 152 individuals (76 couples) having a history of RPL. The cases were analyzed using G-banding and fluorescence in situ hybridization, wherever necessary. Results: Chromosomal abnormalities were observed in 3.2% of the total RPL cases, of which balanced translocations were observed in 4 (80%) individuals and marker chromosome was detected in 1 (20%) individual. All balanced translocations comprised reciprocal translocations, and no cases of Robertsonian translocations were detected in our study. Among reciprocal translocation carriers, three were male and one was female. Polymorphic variants were noted in 8 (5.3%) individuals. Conclusions: Chromosomal analysis is an important etiological investigation in couples with RPL. Balanced translocations are the most commonly detected chromosomal abnormalities in such couples. Thus, these couples are the best candidates for offering prenatal genetic diagnosis, thereby ensuring a better reproductive outcome.